2019
DOI: 10.2807/1560-7917.es.2019.24.26.1900370
|View full text |Cite
|
Sign up to set email alerts
|

Finnish new variant of Chlamydia trachomatis escaping detection in the Aptima Combo 2 assay also present in Örebro County, Sweden, May 2019

Abstract: We identified the first two cases of the Finnish new variant of Chlamydia trachomatis (F-nvCT) beyond Finland in two clinical urogenital specimens in Örebro County, Sweden. These Aptima Combo 2 assay-negative specimens were Aptima Chlamydia trachomatis (CT) assay positive and had the characteristic C1515T mutation in the 23S rRNA gene. From 22 March to 31 May 2019, 1.3% (2/158) of the CT-positive cases in Örebro County were missed because of the F-nvCT. Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 10 publications
2
30
0
1
Order By: Relevance
“…The SNP was verified in both the forward and reverse strands of the sequenced V2 and V3 PCR products, with high quality values (Q-value > 30 by FinchTV, Geospiza). This SNP verifies that AC2 negative but ACT positive specimens contained the Finnish new variant of C. trachomatis (FI-nvCT) [18]. As this was the only mutation detected in the sequenced regions of the 23S rRNA gene, only primer pair V2 was used to amplify 29 additional AC2 negative/equivocal and ACT positive specimens, and the five AC2 positive specimens.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The SNP was verified in both the forward and reverse strands of the sequenced V2 and V3 PCR products, with high quality values (Q-value > 30 by FinchTV, Geospiza). This SNP verifies that AC2 negative but ACT positive specimens contained the Finnish new variant of C. trachomatis (FI-nvCT) [18]. As this was the only mutation detected in the sequenced regions of the 23S rRNA gene, only primer pair V2 was used to amplify 29 additional AC2 negative/equivocal and ACT positive specimens, and the five AC2 positive specimens.…”
Section: Resultsmentioning
confidence: 65%
“…To streamline clinical sample testing with Aptima, Hologic is developing a new assay that specifically targets the FI-nvCT [20,22]. Recently, initial evaluation revealed that two cases of FI-nvCT have been identified in Sweden [18]. As ECDC has been notified and ECDC has informed public health officials in Europe, we expect more information on the epidemiology of FI-nvCT to accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…The Finnish New Variant escaped detection by the Aptima Combo-2 test, which targets the 23S rRNA, but remained detectable by the Aptima CT test, which targets a sequence within the 16S rRNA sequence. The global distribution of the Finnish New Variant has yet to be determined, but it has also been detected in Sweden and further reports seem likely [80]. It is not known whether these isolates were imported from Finland or represent a separate evolutionary event-the former seems more likely given the close proximity of the two countries, but the latter cannot be ruled out until further investigations are completed.…”
Section: Implications On Diagnostic Target Choicementioning
confidence: 98%
“…AC2 negative/equivocal-ACT positive) signalled the presence of the new strain. Data collected in subsequent investigations suggested a recent emergence of FI-nvCT in south-western Finland, Norway and Sweden with relatively low prevalence (ca 1-6%) among patients with C. trachomatis infections [1,[3][4][5]. We have developed and validated a research-use only Aptima-format surveillance NAAT designed specifically to detect the FI-nvCT strain.…”
mentioning
confidence: 99%